An evaluation of the food and drug administration’s expedited pathways - Mayhew, Brian Michael (2016)
Biopharmaceutical development is characterized by challenging regulations, intense competition and significant costs that result in the need for biopharmaceutical companies to consistently produce innovation biopharmaceutical products. The United States Congress has sought to provide a balanced environment that combines significant regulatory oversight by the US Food and Drug Administration (FDA) with market-based incentives (patent protection, exclusivity) and expedited pathways (accelerated approval, breakthrough designation, fast track designation, and priority review) that seek to quickly identify and move innovative new medicines through development that will address unmet medical need and treat serious or life-threatening diseases or conditions. While FDA’s expedited programs are believed to accelerate the development of innovative drug products, the programs have not been formally measured against their intended purpose: more efficient development and regulatory reviews. This thesis research project attempts to effectively measure FDA’s expedited programs by cataloguing FDA approvals from 1987-2015, measuring development and regulatory review time, and drawing conclusions and making recommendations based on the statistical analyses generated from the project.